Information och kommunikation inför tätortsnära avverkning i Västerås - Zettergren, Mattias (SLU/School for Forest Management, 2019)
Forest management and harvesting in urban areas sometimes evoke negative feelings among the public. When Västerås City carried out an extensive thinning of 70 hectares and a final harvesting of two hectares in the district of Gryta in late winter 2018, criticism was directed against Västerås city but also against Mellanskog which carried out the forest operations. The purpose of the study was, based on Västerås, to identify and clarify the flow of information from Västerås City Forest Management and Mellanskog, correlated with local residents' need for information when forest logging is planned in the urban environment. The choice of method in the study consisted of literature studies, several interviews and two questionnaires. There is a conflict for the actual time when information to the public and local residents must be provided. The users (Mellanskog and Västerås city) generally want to provide information at a relatively late stage in order to avoid advocacy but above all to minimize long dialogue processes that are very resource-intensive. There is also a risk when information is provided at an early stage to arouse hopes and aversions linked to the planned forest management which may take a long time before it is carried out or may not be carried out at all. Consumers (the public and the local residents) prefer to receive information with at least one month's advance, but the users instead prioritize an active dialogue with the public and the local residents during harvesting. The dialogues between users and consumers are almost exclusively about individual trees. It is trees that consumers find disturbing in some way but also trees that consumers care about for various reasons. It is of great importance that the machine operators who work in urban environments possess a high communicative competence because the work includes dialogues with the consumers and forms a natural part of the job. A thinning at Bjurhovda in Västerås that was followed in the study, most of the local residents were satisfied with the final result and how the information issues and dialogues were handled with the exception of the short advance.